2015
DOI: 10.1136/openhrt-2014-000183
|View full text |Cite
|
Sign up to set email alerts
|

Infective endocarditis in the Pacific: clinical characteristics, treatment and long-term outcomes

Abstract: IntroductionData on clinical characteristics and outcomes of infective endocarditis (IE) in the Pacific are scarce.MethodsRetrospective hospital-based study in New Caledonia, a high-income country, on patients aged over 18 years with definite IE according to the modified Duke criteria (2005–2010).Results51 patients were included: 31 (60.8%) men; median age of 52.4 years (IQR 33.0–70.0). Left-sided IE accounted for 47 (92.2%) patients: native valve IE in 34 (66.7%) and prosthetic valve IE in 13 (25.5%). The mai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 35 publications
1
5
0
2
Order By: Relevance
“…These relatively younger patients can be explained by the higher incidence of congenital and rheumatic heart diseases in the developing countries. 12,13,15 With the similar proportion of congenital and rheumatic heart diseases in this study (17.8%), it is to be noted that valvular degeneration remains the most commonly encountered predisposing factors in this study (46.6%). This differs with several other studies in southeast Asia which stated that IE is most commonly found in rheumatic heart disease patients.…”
Section: Discussionsupporting
confidence: 64%
See 2 more Smart Citations
“…These relatively younger patients can be explained by the higher incidence of congenital and rheumatic heart diseases in the developing countries. 12,13,15 With the similar proportion of congenital and rheumatic heart diseases in this study (17.8%), it is to be noted that valvular degeneration remains the most commonly encountered predisposing factors in this study (46.6%). This differs with several other studies in southeast Asia which stated that IE is most commonly found in rheumatic heart disease patients.…”
Section: Discussionsupporting
confidence: 64%
“…This result is in accordance with several other studies with a population of both culture positive and negative IE. 2,9,13,15 Majority of patients in this study showed an excellent LV function ranging between 80 and 85%. This finding is in accordance with another study which reported that the majority of patients with IE maintain a good ejection fraction.…”
Section: Discussionmentioning
confidence: 68%
See 1 more Smart Citation
“…En las distintas series, ya sea de pacientes quirúrgicos o del total de EI e independiente del tratamiento, la presencia de EI sobre prótesis valvular representa entre 25% hasta 41% de los casos 10,19,20,[22][23][24] . Si bien lo encontrado en este estudio es significativamente menor, es comparable a 9% a 28% reportado en series nacionales 12 .…”
Section: Discussionunclassified
“…2 However, the underlying heart diseases in patients with infective endocarditis include rheumatic valve disease, degenerative heart valve disease and congenital heart disease. 3 Particularly, in the Republic of Korea, the most common type of underlying heart disease in patients who develop infective endocarditis is rheumatic heart disease, followed by congenital heart disease. 4 Streptococcus viridans is the most commonly isolated microorganism, followed by Staphylococcus aureus.…”
Section: Introductionmentioning
confidence: 99%